Diversity of the coat protein gene of Citrus tristeza virus (CTV) in the Mediterranean region - Djelouah K.; Cerni S.; Fonseca F.; Santos C.; Silva G.; D'Onghia A.M.; Nolasco G. (Citrus tristeza virus and Toxoptera citricidus: a serious threat to the Mediterranean citrus industry, 2009)
Sequence data of the coat protein gene of CTV were retrieved from the GenBank or from tested infected tissues and compiled. A comparison with a comparable set of sequences from worldwide isolates showed a very similar value for the nucleotide diversity and a very similar genetic structure in which the same seven groups of variants are conspicuous. A geographic speciation is not apparent and, probably, differences in the distribution of CTV groups are a result of trade. In countries that usually import propagating material from Spain, the group M predominates while group 3b predominates in countries that import material from Israel.